Elevated miR-10a-5p facilitates cell cycle and restrains adipogenic differentiation via targeting Map2k6 and Fasn, respectively. (30th October 2020) - Wang, Xiaoyu; Zhang, Huifang; Xu, Meixue; Shi, Xin'E; Yang, Gongshe; Sun, Shiduo; Li, Xiao
Abstract: miRNAs are a small class of noncoding RNAs that perform biological functions by regulating the stability or translation of target genes in various biological processes. This study illustrated the role of miR-10a-5p, which is relatively enriched in adipose tissues, using primary mouse preadipocytes as model. With elevated miR-10a-5p expression, the proliferative ability of mouse preadipocytes was significantly enhanced, indicated by increased EdU + cells and G1 /S transition, accompanied by upregulated Cyclin B, Cyclin D and PCNA and downregulated p21 and p27. Meanwhile, the adipogenic differentiation was significantly attenuated by elevated miR-10a-5p, supported by Oil Red O staining and suppressed PPARγ and aP2 expression. Furthermore, Map2k6 and Fasn were predicted to be the target genes of miR-10a-5p in silico, and dual luciferase reporter assay confirmed the direct targeting effects. Western blot analysis results showed that miR-10a-5p specially reduced Map2k6 expression at the proliferative stage without affecting Fasn expression, while significantly restrained Fasn expression with unchanged Map2k6 expression during adipogenic differentiation. Taken together, these results revealed a potential role of miR-10a-5p in adipogenesis and in the treatment of obesity.